Atlas of the heart mapping meaningful connection & the language of human experience - Brown, Brene (New York Random House, 2021)
In Atlas of the Heart, Brown takes us on a journey through 85 of the emotions and experiences that define what it means to be human. As she maps the necessary skills and lays out an actionable framework for meaningful connection, she gives us the language and tools to access a universe of new choices and second chances - a universe where we can share and steward the stories of our bravest and most heartbreaking moments with one another in a way that builds connection. Over the past two decades, Brown's extensive research into the experiences that make us who we are has shaped the cultural conversation and helped define what it means to be courageous with our lives. Atlas of the Heart draws on this research, as well as Brown's singular skills as a researcher/storyteller, to lay out an invaluable, research-based framework that shows us that naming an experience doesn't give the experience more power, it gives us the power of understanding, meaning, and choice. Brown shares, "I want this to be an atlas for all of us, because I believe that, with an adventurous heart and the right maps, we can travel anywhere and never fear losing ourselves. Even when we have no idea where we are
Keywords: Self-actualization (Psychology)